The Level of Depression and Irrational Thoughts among Mothers of Children with Autism Spectrum - Mhaidat, Fatin A.; Alkailanee, Khaledah Kh.M.Zaid; Oudat, Mo'een, A.; Abood, Mohammad Hani Mohammad; Alzghoul, Yazan (Journal of Ecohumanism, 2024)
This study aimed to identify the depression and irrational thoughts level among mothers of children with autism spectrum in Jordan. The researcher applied the descriptive method, and the study population consisted of all the mothers on the autism spectrum who are constant visitors of the Autism Academy of Jordan and have children inside the academy. The sample consisted of (40) mothers of autism spectrum children who were chosen intentionally. The researcher employed the Irrational Beliefs Scale that was used in Al-Nawasreh's study (2017), which consists of 40 items to measure irrational beliefs. Test-retest procedures calculated the scale reliability by calculating Pearson Correlation Coefficient, which amounted (to 0.90). Furthermore, reliability was also verified through the internal consistency according to the Alpha Cronbach equation, where the reliability coefficient reached (0.98). Beck Depression Scale was also used (Abdel Khaleq, 2015 translated that), which is valid, reliable, and suitable for the Jordanian environment. The scale consists of (21) items, and every item consists of 4 statements. The study results showed a medium level of irrational thoughts and a medium level of depression among the mothers of children on the autism spectrum. The results also showed a clear relationship between irrational thoughts and the existence of depressive disorder in the mothers. Depression level